2020
DOI: 10.1101/2020.04.20.029819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identity-by-descent detection across 487,409 British samples reveals fine-scale population structure, evolutionary history, and trait associations

Abstract: 1Detection of Identical-By-Descent (IBD) segments provides a fundamental measure of genetic relatedness and plays a key 2 role in a wide range of genomic analyses. We developed a new method, called FastSMC, that enables accurate biobank-3 scale detection of IBD segments transmitted by common ancestors living up to several hundreds of generations in the past. 4 FastSMC combines a fast heuristic search for IBD segments with accurate coalescent-based likelihood calculations and enables 5 estimating the age of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…In such cases, PCA based on rare variants, which are more informative about recent population history ( Gravel et al, 2011 ; Fu et al, 2013 ; O'Connor et al, 2013 ; O'Connor et al, 2015 ; Mathieson and McVean, 2015 ), would be more effective. Haplotype sharing ( Lawson et al, 2012 ) or identity-by-descent (IBD) segments are similarly informative about recent history ( Palamara et al, 2012 ; Ralph and Coop, 2013 ; Saada et al, 2020 ), and provide an alternative to rare variant PCA when sequence data are not available, or when there are relatively few rare variants to adequately capture the structure, for example in exome sequence data.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, PCA based on rare variants, which are more informative about recent population history ( Gravel et al, 2011 ; Fu et al, 2013 ; O'Connor et al, 2013 ; O'Connor et al, 2015 ; Mathieson and McVean, 2015 ), would be more effective. Haplotype sharing ( Lawson et al, 2012 ) or identity-by-descent (IBD) segments are similarly informative about recent history ( Palamara et al, 2012 ; Ralph and Coop, 2013 ; Saada et al, 2020 ), and provide an alternative to rare variant PCA when sequence data are not available, or when there are relatively few rare variants to adequately capture the structure, for example in exome sequence data.…”
Section: Discussionmentioning
confidence: 99%
“…10 In parallel, fast methods for IBD estimation from tens to hundreds of thousands of individuals have been recently developed for phased [11][12][13][14] and unphased 15,16 genomic data along with scalable clustering methods for the detection of fine-scale community structure. 17,18 Late Bronze and Early Iron Age migrations have been argued to be responsible for the spread of Finnic languages together with a minor Siberian genetic component (Figure 1D) in the circum-Baltic region; 19,20,21 however, it has been less clear how much gene flow and contact over the Gulf of Finland has occurred in the last 2,000 years (Figures 1E and 1F). Linguistic studies have suggested that the differentiation of the Finnic from Finno-Volgaic languages dates back to 3,000-4,000 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Larger sample sizes and data on Mendelian disease diagnoses (as opposed to proxy estimates of risk) will be needed to quantify the risk of recessive disorders for offspring of intra-versus inter-biraderi marriages accurately, noting that our results imply that this differs between biraderi, and that certain disorders may be enriched in particular biraderi as a result of founder effects. Furthermore, future studies of disease genetics in Pakistanis should consider our findings in order to best control for population stratification due to recent structure in genome-wide association studies 16 and potentially to increase power by exploiting the IBD within some groups as a proxy for rare variant sharing 84 .…”
Section: Discussionmentioning
confidence: 99%